Pemberdayaan Warga RW12 Kelurahan Larangan Utara Penggunaan Aplikasi Monitoring Dan Kendali Banjir - Siswanto; Windu Gata; Riefky Sungkar; Muhammad Anif; Ari Saputro; Grace Gata; Subandi; Yuliazmi; Hari Prasetyo, Basuki (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2022)
Community service (PKM) is carried out in the Tangerang area, precisely in the Puri Beta 1 RW 12 Cluster Flamboyan housing. Puri Beta housing consists of three areas, namely Puri Beta Utara, Puri Beta 1, and Puri Beta 2. Housing Puri Beta 1 has many clusters with the condition of the area being traversed starting from the Pine cluster to the Flamboyan cluster, often when heavy rains occur. become a flood prone area. Every year with the rainy season ranging from October to February are the months that need to be observed. In anticipation of this incident, flood control is needed that can provide information on the level of water levels that pass through this cluster, as an early warning so that residents will be alert in the event of a flood. This activity is divided into 3 (three) stages of implementation, namely preparation, implementation, and evaluation. This PKM has been carried out from March 18, 2019 to July 18, 2019, which was carried out offline. In the UAT test, a questionnaire with a Likert scale scale of 5. was used. As a result, the respondents agreed (above 83.3%) that the overall empowerment training for RW12 residents of Larangan Utara Village using flood monitoring and control applications was interesting and understandable.